1971
DOI: 10.1007/bf02346251
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exercise on haematocrit, plasma volume and viscosity in diabetes mellitus

Abstract: Summary. Haematocrit, plasma volume and viscosity were not notably different at rest in fifteen diabetics from those in ten controls. After moderate exercise, plasma volume was reduced and haematoerit was increased significantly more than those in controls. In the diabetic subgroups based on varying degrees of dermal angiopathy, no significant differences were demonstrated. In circulatory steady state during exercise the diabetics responded with a marked increase of systolic blood pressure. The amount of filtr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
1

Year Published

1974
1974
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 13 publications
2
9
1
Order By: Relevance
“…The elevation observed in this study is comparable to the increased serum viscosity observed by Cogan et al (1) and the plasma viscosity increase reported by Isogai et al (5). Other studies have not demonstrated as large an increase (8)(9)(10)(11). A possible explanation for this disagreement may be developed by integrating observations from this study with three previously reported phenomena.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The elevation observed in this study is comparable to the increased serum viscosity observed by Cogan et al (1) and the plasma viscosity increase reported by Isogai et al (5). Other studies have not demonstrated as large an increase (8)(9)(10)(11). A possible explanation for this disagreement may be developed by integrating observations from this study with three previously reported phenomena.…”
Section: Discussionsupporting
confidence: 88%
“…The increased protein level is the result of loss of plasma volume during standing and exercise. The plasma volume decreases more rapidly in diabetes in these circumstances (9). In contrast to the elevated serum protein levels found in ambulatory outpatient diabetics in this study (Table III), hospitalized diabetics have depressed serum protein levels (27).…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…[28],[29],[30] As the osmolarity of the blood increases due to increased sugar level, the capillary permeability increases, thus increasing hematocrit and subsequently the blood viscosity. [31] Similar findings have been observed by Lowe et al [32] and Langer et al [33] that osmotic diuresis is caused by hyperglycemia, leading to decreaaed plasma volume and increased hematocrit. Barnes et al [34] reported that both hematocrit and blood viscosity decreased after institution of good diabetic control.…”
Section: Discussionsupporting
confidence: 81%